KEWENANGAN OTORITAS JASA KEUANGAN DALAM KOMITE STABILITAS SISTEM KEUANGAN INDONESIA (Lex Jurnalica, 2020)
AbstractOne reason for the plan to form a Financial Services Authority is because the government considers Bank Indonesia as the Central Bank to have failed in overseeing the banking sector. This failure can be seen in the economic crisis that hit Indonesia starting in mid-1997. A number of banks were at that time liquidated. Principally, the establishment of the Financial Services Authority so that its supervision becomes integrated and its coordination becomes easier so that regulation regulation becomes more effective. This paper describes the authority of the Financial Services Authority in the Indonesian Financial System Stability Committee. This research is a normative legal research.. Keywords: Financial Services Authority, Financial System Stability Committee.AbstrakSalah satu alasan rencana pembentukan Otoritas Jasa Keuangan adalah karena pemerintah beranggapan Bank Indonesia sebagai Bank Sentral telah gagal dalam mengawasi sektor perbankan. Kegagalan tersebut dapat dilihat pada krisis ekonomi melanda Indonesia mulai pertengahan 1997, Sejumlah bank yang ada pada saat itu dilikuidasi. Prinsipnya, pembentukan Otoritas Jasa Keuangan agar pengawasannya menjadi terintegrasi dan koordinasinya menjadi lebih mudah sehingga pengawasan regulasinya menjadi lebih efektif. Paper ini menggambarkan mengenai kewenangan Otoritas Jasa Keuangan dalam Komite Stabilitas Sistem Keuangan Indonesia. Penelitian ini merupakan penelitian hukum normatif. Kata Kunci : Otoritas Jasa Keuangan, Komite Stabilitas Sistem Keuangan.AbstractOne reason for the plan to form a Financial Services Authority is because the government considers Bank Indonesia as the Central Bank to have failed in overseeing the banking sector. This failure can be seen in the economic crisis that hit Indonesia starting in mid-1997. A number of banks were at that time liquidated. Principally, the establishment of the Financial Services Authority so that its supervision becomes integrated and its coordination becomes easier so that regulation regulation becomes more effective. This paper describes the authority of the Financial Services Authority in the Indonesian Financial System Stability Committee. This research is a normative legal research.. Keywords: Financial Services Authority, Financial System Stability Committee.AbstrakSalah satu alasan rencana pembentukan Otoritas Jasa Keuangan adalah karena pemerintah beranggapan Bank Indonesia sebagai Bank Sentral telah gagal dalam mengawasi sektor perbankan. Kegagalan tersebut dapat dilihat pada krisis ekonomi melanda Indonesia mulai pertengahan 1997, Sejumlah bank yang ada pada saat itu dilikuidasi. Prinsipnya, pembentukan Otoritas Jasa Keuangan agar pengawasannya menjadi terintegrasi dan koordinasinya menjadi lebih mudah sehingga pengawasan regulasinya menjadi lebih efektif. Paper ini menggambarkan mengenai kewenangan Otoritas Jasa Keuangan dalam Komite Stabilitas Sistem Keuangan Indonesia. Penelitian ini merupakan penelitian hukum normatif. Kata Kunci : Otoritas Jasa Keuangan, Komite Stabilitas Sistem Keuangan.